Microenergy acoustic pulse therapy restores urethral wall integrity and continence in a rat model of female stress incontinence. Issue 6 (22nd April 2022) - Tan, Yan; Reed‐Maldonado, Amanda B.; Wang, Guifang; Banie, Lia; Peng, Dongyi; Zhou, Feng; Chen, Yinwei; Wang, Zhao; Lin, Guiting; Lue, Tom F.
Abstract: Objective: To determine the outcomes and mechanisms of microenergy acoustic pulse (MAP) therapy in an irreversible rat model of female stress urinary incontinence. Materials and Methods: Twenty‐four female Sprague–Dawley rats were randomly assigned into four groups: sham control (sham), vaginal balloon dilation and ovariectomy (VBDO), VBDO + β‐aminopropionitrile (BAPN), and VBDO + β‐aminopropionitrile treated with MAP (MAP). MAP therapy was administered twice per week for 4 weeks. After a 1‐week washout period, all 24 rats were evaluated with functional and histological studies. The urethral vascular plexus was examined by immunofluorescence staining with antibodies against collagen IV and von Willebrand factor (vWF). The urethral smooth muscle stem/progenitor cells (uSMPCs) were isolated and functionally studied in vivo and in vitro. Results: Functional study with leak point pressure (LPP) measurement showed that the MAP group had significantly higher LPPs compared to VBDO and BAPN groups. MAP ameliorated the decline in urethral wall thickness and increased the amount of extracellular matrix within the urethral wall, especially in the urethral and vaginal elastic fibers. MAP also improved the disruption of the urethral vascular plexus in the treated animals. In addition, MAP enhanced the regeneration of urethral and vaginal smooth muscle, and uSMPCs could be induced by MAP to differentiate into smooth muscle and neuron‐like cells in vitro. Conclusion: MAP appears to restore urethral wall integrity by increasing muscle content in the urethra and the vagina and by improving the urethral vascular plexus and the extracellular matrix.